PENGEMBANGAN DINAMIKA KELOMPOK TANI MELALUI KERJASAMA - Hanok Untajana (Universitas Musamus, Merauke, Papua, 2011)
Construction of farm groups are more directed to an application of agribusiness system, improvement role, farmer participation with other villagers by improving the corporation between group farm members as weel as the corporation among the farm groups in order to improving their farm produce. Beside that, constructing and developing the dynamic of the groups are expected to help finding the potential, finding the more effectively agricultural solutions for the farm group and easier way to access market information, technology information, financial and other sources information. Good corporation between the group members and also between the groups is the most important thing in reaching the goal which is raising up the farm production. With good corporation also can handle any kinds of conflict between the group member and also between the groups.